SMARTPHONE ADDICTION AMONG COLLEGE STUDENTS: DO SELF-ESTEEM AND SELF-CONTROL PLAY ROLE? - Pramudita, Niken; Sujadi, Eko; Ahmad, Bukhari (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
Smartphone addiction has increasingly emerged as a significant concern among college students. This study aims to investigate the impact of self-esteem and self-control on smartphone addiction within this demographic. Adopting a survey design with a correlational approach, the study involved 130 students selected using convenience sampling. The researchers employed the Smartphone Addiction Scale, Rosenberg Self-Esteem Scale, and Self-Control Scale for data collection. Descriptive statistics were used to examine the variables, followed by hypothesis testing through simple and multiple regression analyses. The results indicate that both self-esteem and self-control negatively affect smartphone addiction, both independently and collectively. Specifically, higher levels of self-esteem and self-control are associated with lower levels of smartphone addiction among participants. This study provides a novel contribution by examining the combined effects of self-esteem and self-control, offering new insights into the roles of these psychological factors in predicting smartphone addiction among Indonesian university students. These findings have significant implications for addressing smartphone addiction through interventions that enhance self-esteem and self-control.